An Empirical Analysis on Supply Chain Problems, Strategy, and Performance with Reference to SMEs - Ganeshan, Hariharan; Suresh, P. (Prabandhan: Indian Journal of Management, 2017)
Free trade, globalization of economy, digital business, and introduction of new technology are posting new challenges to all organizations, especially for small and medium enterprises (SMEs). The purpose of this research paper was to identify the problems faced by SMEs while being a part of the supply chain. The study focused on textile units of SMEs. Around 60 samples were taken, and respondents were also considered as key people of the companies. The data were analyzed using mean, rank, standard deviation, and correlation between independent and dependent variables. To measure improvement in supply chain performance, we considered different measures related to increased production, waste reduction, reduce machine breakdown, low transport and inventory cost, and business performance such as sales and revenue increases. The findings showed that supply chain strategy had a significant relationship with the supply-chain performance.